Photoshop 7 professional photographic techniques. - Aronoff, Janee, ....-; Costello, Nyree, ....-; Cromhout, Gavin, ....- (Birmingham : Friends of ED, 2002)
1.Color and calibration 2.Color correction 3.Adding and subtracting features 4.Restoring and repairing photos 5.Toning and aging images 6.Hand coloring techniques 7.Magazine retouching techniques 8.Creating works of art 9.Infra-red imaging and cross-processing 10.Special effects 11.Preparing images
Keywords: Beeldbewerking; Computer graphics; Photoshop; Webdesign